Inorganic and Layered Perovskites for Optoelectronic Devices - Fakharuddin, Azhar; Shabbir, Umair; Qiu, Weiming; Iqbal, Tahir; Sultan, Muhammad; Heremans, Paul; Schmidt‐Mende, Lukas (Advanced materials (Weinheim), 2019)
Organic–inorganic halide perovskites are making breakthroughs in a range of optoelectronic devices. Reports of >23% certified power conversion efficiency in photovoltaic devices, external quantum efficiency >21% in light‐emitting diodes (LEDs), continuous‐wave lasing and ultralow lasing thresholds in optically pumped lasers, and detectivity in photodetectors on a par with commercial GaAs rivals are being witnessed, making them the fastest ever emerging material technology. Still, questions on their toxicity and long‐term stability raise concerns toward their market entry. The intrinsic instability in these materials arises due to the organic cation, typically the volatile methylamine (MA), which contributes to hysteresis in the current–voltage characteristics and ion migration. Alternative inorganic substitutes to MA, such as cesium, and large organic cations that lead to a layered structure, enhance structural as well as device operational stability. These perovskites also provide a high exciton binding energy that is a prerequisite to enhance radiative emission yield in LEDs. The incorporation of inorganic and layered perovskites, in the form of polycrystalline films or as single‐crystalline nanostructure morphologies, is now leading to the demonstration of stable devices with excellent performance parameters. Herein, key developments made in various optoelectronic devices using these perovskites are summarized and an outlook toward stable yet efficient devices is presented. Inorganic and layered perovskites have broadened research paradigm for a range of optoelectronic devices. Their unique electronic and photophysical properties show that they are an excellent material, leading forefronts of solar cells, light‐emitting diodes, photodetectors, lasers, and beyond. An overview of key research activities for these devices is provided and challenges for their future research are identified.